Estudo e aplicação de conversor multinível híbrido com uma única fonte CC - Vargas, Tadeu (2013)
This study proposes a modulation strategy based on geometric approach for a hybrid multilevel converter with single dc voltage source. This multilevel converter is composed of a three-phase three-level multilevel converter with neutral-point-clamped (NPC) connected in series with single-phase three-level full-bridge cells. The NPC converter operates at the fundamental frequency of the reference signals, and the switching angle of the switches is calculated to ensure that the fundamental component of the NPC converter output voltage is equal to the fundamental component of the reference voltage of the entire hybrid multilevel converter. Therefore, the full-bridge cells, which operate with pulse width modulation (PWM), do no process active power and they can be supplied by capacitors. However, to guarantee that the full-bridge cells operate in the linear region a common mode voltage is added on its reference signals. This work uses a systematic methodology for obtaining the region of possible values of common mode voltage to ensure the operation of the full-bridge cells in the linear region, it being possible to maintain the DC bus voltages regulated without distorting the output line-to-line voltages. Moreover, this study applies the hybrid multilevel converter with single DC source as input stage (rectifier) of medium-voltage variable speed drive systems, becoming an alternative for applications that require energy regeneration, high efficiency and input power factor as well as a satisfactory dynamic response. Simulation and experimental results are included to validate the analyzes presented in this work.